The MOSDEF-LRIS Survey: The connection between massive stars and ionized gas in individual galaxies at z ∼ 2. Issue 2 (26th September 2020) - Topping, Michael W; Shapley, Alice E; Reddy, Naveen A; Sanders, Ryan L; Coil, Alison L; Kriek, Mariska; Mobasher, Bahram; Siana, Brian
ABSTRACT: We present constraints on the massive star and ionized gas properties for a sample of 62 star-forming galaxies at z ∼ 2.3. Using BPASS stellar population models, we fit the rest-UV spectra of galaxies in our sample to estimate age and stellar metallicity which, in turn, determine the ionizing spectrum. In addition to the median properties of well-defined subsets of our sample, we derive the ages and stellar metallicities for 30 high-SNR individual galaxies – the largest sample of individual galaxies at high redshift with such measurements. Most galaxies in this high-SNR subsample have stellar metallicities of 0.001 < Z * < 0.004. We then use Cloudy + BPASS photoionization models to match observed rest-optical line ratios and infer nebular properties. Our high-SNR subsample is characterized by a median ionization parameter and oxygen abundance, respectively, of log ( U )med = −2.98 ± 0.25 and 12 + log (O/H)med = 8.48 ± 0.11. Accordingly, we find that all galaxies in our sample show evidence for α-enhancement. In addition, based on inferred log ( U ) and 12 + log (O/H) values, we find that the local relationship between ionization parameter and metallicity applies at z ∼ 2. Finally, we find that the high-redshift galaxies most offset from the local excitation sequence in the BPT diagram are the most α-enhanced. This trend suggests that α-enhancement resulting in a harder ionizing spectrum at fixed oxygen abundance is a significant driver of the high-redshift galaxy offset on the BPT diagram relative to local systems. The ubiquity of α-enhancement among z ∼ 2.3 star-forming galaxies indicates important differences between high-redshift and local galaxies that must be accounted for in order to derive physical properties at high redshift.